Lithuanian cluster of sea economics – instrument of sustainable regional development - Grublienė, Violeta (Business, Management and Economics Engineering, 2010)
The article analyses problems of cluster’s formation in Lithuania. The reasons why clusters in Lithuania are evolving slowly are described in this article. Also cluster’s development process in a logical sequence is submitted. The article accented that the Lithuanian cluster’s policy principles should assess the specific Lithuanian conditions, the positive foreign experience and strategic objectives of competitiveness.Lithuanian status of fisheries sector is estimated. Also the main problems in this sector are named: complexity of management, decreasing of fishing quota, shorter season of cod fishing, economic problems. The article made assumptions that the clustering process should ensure more sustainable development of the sector, a new operational quality creating the ability to compete at lower prices and innovation. Also it was emphasized that clustering processes should assess such factors as: sector’s culture, competitive opportunities and sustainable development of the region.During formation of this cluster it is recommended to assess the fisheries sector as the component of Lithuanian maritime economy. Lithuanian maritime cluster should be developed allowing for common features inherent in clusters, assessing sustainable development principles of the sector. In this way Lithuanian maritime cluster combines not only the fisheries sector but also the activities characterized by Lithuanian maritime economy. Article in Lithuanian. Lietuvos jūrų ūkio klasteris – darnios regiono plėtros instrumentas